A new methodology for flexible mine design - Groeneveld, B.; Topal, Erkan; Leenders, B. (2018)
© The Australasian Institute of Mining and Metallurgy 2018. All rights are reserved. Uncertainty and risk are invariably embedded in every mining project. Mining companies endeavouring to maximise their return for shareholders make important strategic decisions which take years or even decades to 'play out'. Therefore, developing a model that analyses the potential payoff of a decision based on current fixed assumptions is severely flawed. A model that incorporates uncertainty and is able to adapt, almost certainly will help deliver a design with a better risk-return profile. In this paper, a new approach is developed in order to have a design that is flexible and able to adapt with change. This is achieved by developing a mixed integer programming model that determines the optimal design for simulated stochastic parameters. This research has incorporated optionality (flexibility) in relation to mining, stockpiling, processing plant and port capacity. The results are promising and are helping decision makers to think in terms of value, risk and frequency of execution.